2017
DOI: 10.1186/s13256-017-1446-5
|View full text |Cite
|
Sign up to set email alerts
|

Osteitis of the radius following Bacillus Calmette–Guérin vaccination at birth: a case report

Abstract: BackgroundThe Bacillus Calmette–Guérin vaccine, which is used for the prevention of tuberculosis, is considered protective against the severe forms of childhood tuberculosis. However, some serious adverse reactions including osteitis of the long bones can occur.Case presentationWe report a case of an 18-month-old Sudanese girl who presented at the age of 3 months with swelling of her left forearm following Bacillus Calmette–Guérin vaccination administered at birth. Radiological and histological investigations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Interestingly, the study from Thailand reported, in addition to five localised BCG osteitis cases, also three cases with disseminated BCG infection, and two of them had severe combined immunodeficiency and one had Wiskott-Aldrich syndrome. 8 Thus, the systematic review, 2 and the basic and outcome data of the 222 Finnish BCG osteitis patients 3,4,21,25 and the data of the 93 new patients included in the present review [5][6][7][8][9][10] confirm that there are no major immunological problems in the BCG osteitis patients, if the infection is not disseminated, and if multiple or recurrent lesions are not present.…”
Section: Immunologymentioning
confidence: 74%
See 3 more Smart Citations
“…Interestingly, the study from Thailand reported, in addition to five localised BCG osteitis cases, also three cases with disseminated BCG infection, and two of them had severe combined immunodeficiency and one had Wiskott-Aldrich syndrome. 8 Thus, the systematic review, 2 and the basic and outcome data of the 222 Finnish BCG osteitis patients 3,4,21,25 and the data of the 93 new patients included in the present review [5][6][7][8][9][10] confirm that there are no major immunological problems in the BCG osteitis patients, if the infection is not disseminated, and if multiple or recurrent lesions are not present.…”
Section: Immunologymentioning
confidence: 74%
“…BCG osteitis cases which were reported from 2013 to June 2019 were searched in PubMed using the terms ‘BCG osteitis’, ‘BCG osteomyelitis’ and ‘BCG vaccination complications’. Six reports including 102 patients were found: one case from France, 5 one case from Sudan, 6 21 cases from Korea, 7 five cases from Thailand, 8 three cases from Mexico 9 and 71 cases from Taiwan 10 . Nine of the BCG osteitis cases reported in 2013‐2019 were already included, and 93 were not included in the systematic review published in 2015 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations